On the analysand's need to know the real person of the analyst - K (Journal of analytical psychology, 2014)
Based on personal experience the main part of this paper explores the theme of the analysand's need to know the real person of the analyst and the importance, on occasion, of the analyst's disclosure of subjectivity. The concluding part offers suggestions about working with analysands where there is early emotional damage and deficits in relationship.